2021
DOI: 10.7759/cureus.16712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genicular Nerve Block in Combination With Adductor Canal Block in Both Primary and Revision Total Knee Arthroplasty: A Retrospective Case Series

Abstract: The management of pain in patients undergoing total knee arthroplasty (TKA) for chronic knee osteoarthritis (OA) has remained a challenge for the anesthesiologist regarding regional anesthesia as no single regional technique is adequate with regard to balancing effective analgesia with minimal muscle weakness. Severe postoperative pain following TKA has been shown to negatively impact patient outcomes and mortality. The genicular nerve block has recently been demonstrated to provide effective analgesia to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…RCT research by Tan et al also reported a significant improvement of VAS scores 2-24 hours after the ACB procedure and this result was similar to the Femoral Nerve Block (FNB) procedure [17]. Retrospective studies by [13] compared ACB procedures with a combination of ACB and GNB. The study found an improving VAS scores in both groups, while the ACB and GNB combination groups had a lower VAS score than ACB only [13].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…RCT research by Tan et al also reported a significant improvement of VAS scores 2-24 hours after the ACB procedure and this result was similar to the Femoral Nerve Block (FNB) procedure [17]. Retrospective studies by [13] compared ACB procedures with a combination of ACB and GNB. The study found an improving VAS scores in both groups, while the ACB and GNB combination groups had a lower VAS score than ACB only [13].…”
Section: Discussionmentioning
confidence: 79%
“…Based on the analysis test on the VAS score variable, significance between the ACB and GNB procedures (P <0.05) was decided. This is because the ACB procedure targets the saphenous nerve, medial cutaneous femoral nerve, medial vastus nerve, and the articular branch of the obturator nerve [13]. There is no other study that compares the post procedure VAS score with ACB and GNB.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no single regional anesthesia technique can provide ideal analgesia, especially without any motor weakness after TKA [14]. Some patients will not achieve adequate posterior knee analgesia as ACB pain relief is primarily limited to the anterior capsule of the knee [6,14].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no single regional anesthesia technique can provide ideal analgesia, especially without any motor weakness after TKA [14]. Some patients will not achieve adequate posterior knee analgesia as ACB pain relief is primarily limited to the anterior capsule of the knee [6,14]. Infiltration between the Popliteal Artery and Capsule of the posterior Knee (IPACK) and genicular nerve block (GNB) combined with ACB has been studied to cover this problem with promising results [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation